Magnetic resonance imaging in the diagnosis of type 1 dermoid sinus in two Rhodesian ridgeback dogs - Rahal, Sheila [UNESP]; Mortari, Ana Carolina [UNESP]; Yamashita, Seizo [UNESP]; Filho, Miltom Morishin [UNESP]; Hatschbac, Eduardo [UNESP]; Sequeira, Júlio Lopes [UNESP] (My University, 2008)
Two cases of type 1 dermoid sinus in Rhodesian ridgebacks are described, with emphasis on the use of magnetic resonance imaging (MRI) in the diagnosis and delineation of the lesions. Magnetic resonance imaging was useful in identifying fluid-filled structures, fibrous capsules, and sinus tracts, but was not able to identify the termination of the tracts.